Estimation of Clinch Joint Characteristics Based on Limited Input Data Using Pre-Trained Metamodels - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (AI)
Given strict emission targets and legal requirements, especially in the automotive industry, environmentally friendly and simultaneously versatile applicable production technologies are gaining importance. In this regard, the use of mechanical joining processes, such as clinching, enable assembly sheet metals to achieve strength properties similar to those of established thermal joining technologies. However, to guarantee a high reliability of the generated joint connection, the selection of a best-fitting joining technology as well as the meaningful description of individual joint properties is essential. In the context of clinching, few contributions have to date investigated the metamodel-based estimation and optimization of joint characteristics, such as neck or interlock thickness, by applying machine learning and genetic algorithms. Therefore, several regression models have been trained on varying databases and amounts of input parameters. However, if product engineers can only provide limited data for a new joining task, such as incomplete information on applied joining tool dimensions, previously trained metamodels often reach their limits. This often results in a significant loss of prediction quality and leads to increasing uncertainties and inaccuracies within the metamodel-based design of a clinch joint connection. Motivated by this, the presented contribution investigates different machine learning algorithms regarding their ability to achieve a satisfying estimation accuracy on limited input data applying a statistically based feature selection method. Through this, it is possible to identify which regression models are suitable to predict clinch joint characteristics considering only a minimum set of required input features. Thus, in addition to the opportunity to decrease the training effort as well as the model complexity, the subsequent formulation of design equations can pave the way to a more versatile application and reuse of pretrained metamodels on varying tool configurations for a given clinch joining task.
Keywords: Industrial and Manufacturing Engineering

Das Leben nehmen oder den Tod geben – Selbstbestimmtes Sterben auf der Schwelle von Utopie zur Realität? - Harmening, Anda-Lisa Martha Josephine Anna (Sonderausgabe des Jahrbuchs für internationale Germanistik 2022)

Wissenstransfer als Aufgabe, Herausforderung und Chance kulturwissenschaftlicher Forschung

Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre

Directing Pandemic Attention: Dystopian Corona Narratives and the Nation in British Media and Politics - Tönnies, Merle; Flotmann-Scholz, Christina (Anglistik: International Journal of English Studies)

Anger, Anxiety and Hope: The Complicit Realities and Engaged/ing Communities of Contemporary Briitsh Dys/Utopian Theatre - Tönnies, Merle; Voigts, Eckart (Twenty-First Century Anxieties: Dys/Utopian Spaces and Contexts in Contemporary British Theatre (CDE Studies))

Weil wir tatsächlich nicht voneinander wussten, was jeder Einzelne so an verborgenen Schätzen bringt - Lütje-Klose , Birgit; Grüter, Sandra; Neumann, Phillip; Weber, Antonia; Goldan, Janka; Gorges, Julia; Wild, Elke (Qualifizierung für Inklusion. Sekundarstufe)

Design and investigation of a metalens for efficiency enhancement of laser-waveguide coupling in a limited space system - laeim, Huddad; Schlickriede, Christian; Chaisakul, Papichaya; Chattham, Nattaporn; Panitchakan, Hathai; Siangchaew, Krisda; Zentgraf, Thomas; Pattanaporhratana, Apichart (Metamaterials, Metadevices, and Metasystems 2022)

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; Villa, Francesco Della (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Cortical responses to sport-specific stimuli in a standing stop signal task - Scharfen, Hans-Erik; Lehmann, Tim; Büchel, Daniel; Baumeister, Jochen (Psychology of Sport and Exercise)
Keywords: Applied Psychology

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehman, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Abstract Background The outcome after ACL reconstruction (ACLR) is in general disappointing with unacceptable number of athletes that do not return to pre-injury level of sports, high re-injury rates, early development of osteoarthritis and shorter careers. Athletes after ACLR have high expectation to return to sports which is in contrast with the current outcomes. The aim of this manuscript is to present an overview of factors that are needed to be incorporated and to personalize the rehabilitation process for an athlete who has undergone an ACLR. Level of evidence 4.
Keywords: Orthopedics and Sports Medicine

Correction: Return to sports after ACL injury 5 years from now: 10 things we must do - Gokeler, Alli; Grassi, Alberto; Hoogeslag, Roy; van Houten, Albert; Lehman, Tim; Bolling, Caroline; Buckthorpe, Matthew; Norte, Grant; Benjaminse, Anne; Heuvelmans, Pieter; Di Paolo, Stefano; Tak, Igor; et al. (Journal of Experimental Orthopaedics)
Keywords: Orthopedics and Sports Medicine

Comparing lab and field agility kinematics in young talented female football players: Implications for ACL injury prevention - Di Paolo, Stefano; Nijmeijer, Eline; Bragonzoni, Laura; Dingshoff, Evelien; Gokeler, Alli; Benjaminse, Anne (European Journal of Sport Science)
Keywords: Orthopedics and Sports Medicine; Physical Therapy; Sports Therapy and Rehabilitation; General Medicine

Towards Situational Process Management for Professional Education Programmes - Wolters, Dennis; Engels, Gregor (Product-Focused Software Process Improvement)

ARCH-COMP22 Category Report: Stochastic Models - Abate, Alessandro; Blom, Henk; Delicaris, Joanna; Haesaert, Sofie; Hartmanns, Arnd; van Huijgevoort, Birgit; Lavaei, Abolfazl; Ma, Hao; Niehage, Mathis; Remke, Anne; Schön, Oliver; Schupp, Stefan; et al. (EPiC Series in Computing)
This report presents the results of a friendly competition for formal verification and policy synthesis of stochastic models. It also introduces new benchmarks and their properties within this category and recommends next steps for this category towards next year’s edition of the competition. In comparison with tools on non-probabilistic models, the tools for stochastic models are at the early stages of development that do not allow full competition on a standard set of benchmarks. We report on an initiative to collect a set of minimal benchmarks that all such tools can run, thus facilitating the comparison between efficiency of the implemented techniques. The friendly competition took place as part of the workshop Applied Verification for Continuous and Hybrid Systems (ARCH) in Summer 2022.

Model Predictive Torque Control for Permanent Magnet Synchronous Motors Using a Stator-Fixed Harmonic Flux Reference Generator in the Entire Modulation Range - Brosch, Anian; Wallscheid, Oliver; Böcker, Joachim (IEEE Transactions on Power Electronics)
Keywords: Electrical and Electronic Engineering

Multi-Objective Physics-Guided Recurrent Neural Networks for Identifying Non-Autonomous Dynamical Systems - Schön, Oliver; Götte, Ricarda-Samantha; Timmermann, Julia (arXiv:2204.12972)
While trade-offs between modeling effort and model accuracy remain a major concern with system identification, resorting to data-driven methods often leads to a complete disregard for physical plausibility. To address this issue, we propose a physics-guided hybrid approach for modeling non-autonomous systems under control. Starting from a traditional physics-based model, this is extended by a recurrent neural network and trained using a sophisticated multi-objective strategy yielding physically plausible models. While purely data-driven methods fail to produce satisfying results, experiments conducted on real data reveal substantial accuracy improvements by our approach compared to a physics-based model.

Correct-by-Design Control of Parametric Stochastic Systems - Schön, Oliver; Huijgevoort, Birgit van; Haesaert, Sofie; Soudjani, Sadegh (arXiv:2210.08269)
This paper addresses the problem of computing controllers that are correct by design for safety-critical systems and can provably satisfy (complex) functional requirements. We develop new methods for models of systems subject to both stochastic and parametric uncertainties. We provide for the first time novel simulation relations for enabling correct-by-design control refinement, that are founded on coupling uncertainties of stochastic systems via sub-probability measures. Such new relations are essential for constructing abstract models that are related to not only one model but to a set of parameterized models. We provide theoretical results for establishing this new class of relations and the associated closeness guarantees for both linear and nonlinear parametric systems with additive Gaussian uncertainty. The results are demonstrated on a linear model and the nonlinear model of the Van der Pol Oscillator.

Scikit-Weak: A Python Library for Weakly Supervised Machine Learning - Campagner, Andrea; Lienen, Julian; Hüllermeier, Eyke; Ciucci, Davide (Lecture Notes in Computer Science)

Review on: Daniel Benedikt Stienen: Verkauftes Vaterland - Schönhärl, Korinna (Sehepunkte)

Review on: Sven Steinmo: Willing to Pay? A Reasonable Choice Approach - Schönhärl, Korinna (HSozKult)

‚Understand what’s happening within‘. Selbstkontrolle mit Personenwaage, Wearable und habit tracker - Schloots, Franziska Margarete (ffk Journal)
Mit steigenden Optimierungsanforderungen an das Individuum wächst auch das indivi- duelle Bedürfnis nach Kontrolle. Dieses kann u. a. durch self tracking-Technologien erfüllt werden. Anhand von drei Fallbeispielen – der Personenwaage, dem Wearable und dem habit tracker – zeigt dieser Aufsatz, wie sich medienbasierte Selbsttechnologien im historischen Verlauf intensiviert und stärker in den Alltag integriert haben. Ein besonderer Fokus liegt dabei auf der Ambivalenz dieser Medien: Ermöglichen sie auf der einen Seite zwar eine Selbstkontrolle und stellen so potenziell sta- bilisierende Ressourcen für das Individuum dar, schaffen sie auf der anderen Seite auch neue Anforderungen, die es zu erfüllen gilt.
Keywords: self-tracking; Selbsttechnologien; Wearable; Bullet Journal; Personenwaage; Selbstvermessung

Using second-order information in gradient sampling methods for nonsmooth optimization - Gebken, Bennet (arXiv:2210.04579)
In this article, we show how second-order derivative information can be incorporated into gradient sampling methods for nonsmooth optimization. The second-order information we consider is essentially the set of coefficients of all second-order Taylor expansions of the objective in a closed ball around a given point. Based on this concept, we define a model of the objective as the maximum of these Taylor expansions. Iteratively minimizing this model (constrained to the closed ball) results in a simple descent method, for which we prove convergence to minimal points in case the objective is convex. To obtain an implementable method, we construct an approximation scheme for the second-order information based on sampling objective values, gradients and Hessian matrices at finitely many points. Using a set of test problems, we compare the resulting method to five other available solvers. Considering the number of function evaluations, the results suggest that the method we propose is superior to the standard gradient sampling method, and competitive compared to other methods.

Genotype-phenotype mapping with polyominos made from DNA origami tiles - Dreher, Yannik; Fichtler, Julius; Karfusehr, Christoph; Jahnke, Kevin; Xin, Yang; Keller, Adrian; Göpfrich, Kerstin (Biophysical Journal)
Keywords: Biophysics

Enhanced corrosion resistance of epoxy-films on ultra-thin SiOx PECVD film coated laser surface melted Al-alloys - Varghese, J.; Vieth, P.; Xie, X.; Grundmeier, Guido (SN Applied Sciences)
Abstract The influence of ultra-thin SiO x plasma deposited films on the corrosion resistance of adhesive films on a laser surface melted 7075 aluminium alloy was investigated by means of complementary techniques in comparison to the just laser surface melted state. Laser surface melting (LSM) was performed using a continuous wave mode at a wavelength of 1064 nm. Ultra-thin plasma polymer films were deposited from a mixture of hexamethyldisilane (HMDSO), oxygen, and argon by means of an audio-frequency glow discharge. The surface morphology and surface chemistry compositions were investigated by employing field emission scanning electron microscopy, energy-dispersive X-ray spectroscopy (EDX), diffuse reflection infrared Fourier transform spectroscopy, and X-ray photoelectron spectroscopy. The corrosion resistance of plasma polymer coated LSM Al-7075 alloy was studied using linear sweep voltammetry and electrochemical impedance spectroscopy in a chloride-containing electrolyte. The electrochemical studies showed an improved corrosion resistance for plasma film-coated alloys compared to the just laser surface melted state. To study the corresponding surface adhesive properties, the samples were coated with an epoxy amine adhesive. 90°-peel test under humid conditions confirmed the improvement of interfacial wet-adhesion corrosion tests showed a strong improvement of the delamination resistance of adhesives caused by the ultra-thin interfacial SiO x -films.
Keywords: General Earth and Planetary Sciences; General Physics and Astronomy; General Engineering; General Environmental Science; General Materials Science; General Chemical Engineering

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; Arcos, Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos, Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg K.N. (Advanced Materials Interfaces)
Keywords: General Medicine

Combined in-situ attenuated total reflection-Fourier transform infrared spectroscopy and single molecule force studies of poly(acrylic acid) at electrolyte/oxide interfaces at acidic pH - Neßlinger, Vanessa; Orive, Alejandro G.; Meinderink, Dennis; Grundmeier, Guido (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos, Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Mentoring-Programm zur Einarbeitung neuer Lehrbeauftragter. Format, Inhalte und Evaluationsergebnisse. - Behrent, Sigrid (Sprachen. Politik. Sprachenpolitik. Der Beitrag der Sprachenzentren zur Hochschule der Zukunft. Dokumentation der 31. Arbeitstagung vom 5.-7. März 2020 an der Europa-Universität Viadrina in Frankfurt (Oder))

Auswirkungen unterschiedlicher Erwärmstrategien auf die quasistatische und zyklische Belastbarkeit von infrarotgeschweißten, glasfaserverstärkten Thermoplastbauteilen - Schöppner, Volker; Gevers, Karina; Schraa, L.; Töws, P. (Joining Plastics)

A Reverse Engineering Approach for Calibrating Frictional Behavior of Contact Models for Numerical Simulation of Solids Conveying in Extruders - Schöppner, Volker; Brüning, Florian; Sommer, L.

Auswirkungen des Vorscherungseinflusses im Extrusionsprozess auf die rheologischen Kennwerte gefüllter Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)

Auf der Welle zum Mischerfolg - Schöppner, Volker; Dörner, Marius; Frank, Maximilian; Schall, Christoph Wilhelm Theodor (Kunststoffe)

BMC-Spritzgießen bricht die Glasfaser - Moritzer, Elmar; Scholle, Maximilian

Influence of process parameter on fiber quality during fiber recycling through thermal fiber recovery - Moritzer, Elmar; Scholle, Maximilian; Tölle, Lisa; Bomm, J. (RFP Rubber Fibres Plastics)

Einfluss der Prozessführung auf die Faserqualität beim Faserrecycling mittels thermischer Faserrückgewinnung - Moritzer, Elmar; Scholle, Maximilian; Tölle, Lisa; Bomm, J. (GAK - Gummi Fasern Kunststoffe)

Estimation and correction of non-isothermal effects of carbon black-filled rubber compounds in viscosity measurements - Schöppner, Volker; Kleinschmidt, Dennis

Filling and Flow Behavior of Novel Wood-Filled Thermoplastic Elastomers - Moritzer, Elmar; Richters, Maximilian

Investigations on the Influence of Viscoelasticity on the Swell Behaviour and Flow Instabilities of Carbon Black-Filled Rubber Compounds - Schöppner, Volker; Kleinschmidt, Dennis; Hopmann, C.; Limper, A.; Fey, F.; Facklam, M.; Schön, M.

Investigating Different Methods for Numerical Simulation of Temperature Development in a Feed Section of a Single-Screw Extruder - Schöppner, Volker; Brüning, Florian

Integration of IR Based Inline Measurement Systems of the Surface Temperature of Square Hollow Profiles in an Extrusion Process - Schöppner, Volker; Köllermeier, Jonas

Investigation of the Pressure-Throughput Behavior of Different Spiral Shearing Sections on an Analytical and Simulative Basis - Schöppner, Volker; Frank, Maximilian

Modelling of the material degradation of polypropylene on the co-rotating twin-screw extruder - Schöppner, Volker; Altepeter, Matthias; Wanke, S.

Weiterentwicklung eines Verfahrens zur Korrektur von Wandgleiteffekten im Rahmen rheologischer Messungen an gefüllten Kautschukmischungen - Schöppner, Volker; Kleinschmidt, Dennis; Nillius, U.; Hopmann, C. (GAK)

Rückführung zerkleinerter Organobleche - Moritzer, Elmar; Kröker, M.; Scholle, Maximilian

Teilchen-Kunde - Stäube beim mechanischen Recycling faserverstärkter Thermoplaste - Hopp, Matthias; Tölle, Lisa

Vorteilhaftes Prozessverhalten von Wave-Schnecken - Schall, Christoph Wilhelm Theodor

Modeling Business Models: A cross-disciplinary Analysis of Business Model Modeling Languages and Directions for Future Research - Szopinski, Daniel; Massa, Lorenzo; John, Thomas; Kundisch, Dennis; Tucci, Christopher (Communications of the Association for Information Systems)

Non-Lie subgroups in Lie groups over local fields of positive characteristic - Glöckner, Helge (p-Adic Numbers, Ultrametric Analysis, and Applications)
Keywords: 20Exx; 22Exx; 32Cxx

Manifolds of mappings on Cartesian products - Glöckner, Helge; Schmeding, Alexander (Annals of Global Analysis and Geometry)
Keywords: 58D15; 22E65; 26E15; 26E20; 46E40; 46T20; 58A05

Aspects of differential calculus related to infinite-dimensional vector bundles and Poisson vector spaces - Glöckner, Helge (Axioms)
We prove various results in infinite-dimensional differential calculus that relate the differentiability properties of functions and associated operator-valued functions (e.g., differentials). The results are applied in two areas: (1) in the theory of infinite-dimensional vector bundles, to construct new bundles from given ones, such as dual bundles, topological tensor products, infinite direct sums, and completions (under suitable hypotheses); (2) in the theory of locally convex Poisson vector spaces, to prove continuity of the Poisson bracket and continuity of passage from a function to the associated Hamiltonian vector field. Topological properties of topological vector spaces are essential for the studies, which allow the hypocontinuity of bilinear mappings to be exploited. Notably, we encounter kR-spaces and locally convex spaces E such that E×E is a kR-space.

Birkhoff decompositions for loop groups with coefficient algebras - Glöckner, Helge (arXiv:2206.11711)
Starting with a finite-dimensional complex Lie algebra, we extend scalars using suitable commutative topological algebras. We study Birkhoff decompositions for the corresponding loop groups. Some results remain valid for loop groups with valued in complex Banach-Lie groups.

Thermal influence of resistance spot welding on nearby overmoulded plastic metal joints - Wippermann, Jan; Meschut, Gerson; Koschukow, Wikentji; Liebsch, Alexander; Gude, Maik; Kolbe, Björn; Minch, Steven (IIW2022, Annual Assembly, Commission III)

Characterization of additively manufactured plastic components for direct screwing - Moritzer, Elmar; Held, Christian

Flexible Teilautomatisierung des robotergestützten mechanischen Fügens - Wippermann, Jan; Meschut, Gerson; Stepputat, Marten; Flügge, Wilko (12. Gemeinsames Kolloquium zur Mechanischen Fügetechnik)

Plasmaaktivierung fehlgeschlagen! - Moritzer, Elmar; Rauen, Dennis (Kunststoffe)

Classification characteristics of fine motor experts based on electroencephalographic and force tracking data - Gaidai, Roman; Gölz, Christian Johannes; Mora, K.; Rudisch, J.; Reuter, E.-M.; Godde, B.; Reinsberger, C.; Voelcker-Rehage, C.; Vieluf, S. (Brain Research)
Keywords: Developmental Biology; Neurology (clinical); Molecular Biology; General Neuroscience

Berufsvorbereitende Sprachförderung. Wie werden Schülerinnen und Schüler fit für den Beruf? - Zierau, Cornelia; Jung, Ulla (Fördermagazin: Berufsbezogene Sprachbildung und Sprachförderung Heft 3/2022)

Fördermagazin: Berufsbezogene Sprachbildung und Sprachförderung Heft 3/2022

Inszenierungen von Adoleszenz und Alterität in Wolfgang Herrndorfs Roman „Tschick“ - Zierau, Cornelia (Adoleszenz und Alterität. Synergien aktueller Ansätze der interkulturellen Literaturwissenschaft und Literaturdidaktik. (im Druck))

V-Edge: Virtual Edge Computing as an Enabler for Novel Microservices and Cooperative Computing - Dressler, Falko; Chiasserini, Carla Fabiana; Fitzek, Frank H. P.; Karl, Holger; Lo Cigno, Renato; Capone, Antonio; Casetti, Claudio Ettore; Malandrino, Francesco; Mancuso, Vincenzo; Klingler, Florian; Rizzo, Gianluca A. (IEEE Network)

Oddly satisfying und die Genugtuung der Anschaulichkeit - Diester, Michel (Rabbit Eye - Zeitschrift für Filmforschung, 013)

Risk allocation through securitization – Evidence from non-performing loans - Wengerek, Sascha Tobias; Hippert, Benjamin; Uhde, André (The Quarterly Review of Economics and Finance)
Employing a unique and hand-collected sample of 648 true sale loan securitization transactions issued by 57 stock-listed banks across the EU-12 plus Switzerland over the period from 1997 to 2010, this paper empirically analyzes the relationship between true sale loan securitization and the issuing banks’ non-performing loans to total assets ratios. Overall, we provide evidence for a negative impact of securitization on NPL exposures suggesting that banks predominantly used securitization as an instrument of credit risk transfer and diversification. In addition, the analysis at hand reveals a time-sensitive relationship between securitization and NPL exposures. While we observe an even stronger NPL-reducing effect through securitization during the non-crisis periods, the effect reverses during and after the global financial crisis suggesting that banks were forced to provide credit enhancement and employ securitization as a funding management tool. Along with the results from a variety of sensitivity analyses our study provides important implications for the recent debate on reducing NPL exposures of European banks by revitalizing the European securitization market.
Keywords: European Banking; Non-performing Loans; Securitization

Franz von Fürstenbergs Konzeption der Universität Münster als aufgeklärte Überbietung Paderborns - Süßmann, Johannes (Gründung und Aufbau der Universität Münster, 1773–1818. Zwischen katholischer Aufklärung, französischen Experimenten und preußischem Neuanfang)

[Art.] Idylle und Natur in Aufklärung und Empfindsamkeit - Büttner, Nils; Süßmann, Johannes (Handbuch Idylle. Verfahren – Traditionen – Theorien)

Gegenreformation und verpaßte Aufklärung. Die Gründung der Academia Theodoriana 1614 und ihre Entwicklung im 17. und 18. Jahrhundert. Videographierter Vortrag für die Ringvorlesung zum fünfzigjährigen Bestehen der Gesamthochschule Paderborn am 13. April 2022 in Paderborn - Süßmann, Johannes

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Clinching is a very cost-efficient method for joining two or more sheets made of identical or different materials. However, the current evaluation methods cannot confirm the critical geometrical features of joints such as neck thickness, undercut, and bottom thickness. Furthermore, the effects caused by joining process such as elastic deformation and crack-closure are significant for the joining quality, but often earn insufficient attention. Therefore, computed tomography (CT) and Transient Dynamic Analysis (TDA) as an ultrasonic testing and evaluation procedure are combined to overcome the obstacles mentioned above. In order to have a well-defined and reproducible typical geometrical error in clinching, specimens with a pre-specified lateral offset of the punch with 0.1 mm, 0.2 mm are as well as with no lateral offset are investigated using CT. The specimens are treated with conductive copper varnish in varying intensities to support the two sheets' distinguishability in the CT measurement. The subsequently extracted surfaces from CT-scan data are used to create three-dimensional models for a numerical Transient Dynamic Analysis. Hereby, a harmonic force is applied to one sheet and the transferred energy is determined at the opposite side of the clinch point on the other sheet. The transmitted energy can be used as a quantitative measure for the joining quality. This setup is simulated by means of Finite-Element-Method and the specimens are investigated experimentally using a piezo actuator and a piezo sensor. The novelty of the results presented here is the completely non-destructive investigation of joint specimen by CT of similar materials with a contrast given foil in between the sheets and the subsequent TDA, which can easily detect difference between the specimens by evaluation of the energy dissipation of the joints.

Joining of continuous fiber reinforced thermoplastic/steel hybrid parts via undercutting pin structures and infrared heating - Popp, J.; Drummer, D. (Journal of Advanced Joining Processes)
Continuous fiber reinforced thermoplastics (CFRT)/steel hybrid parts offer promising properties and possibilities, which can exceed the capabilities of both individual materials. In this case, the joining operation presents the main challenge. This paper studies the direct pin pressing where metallic pins with undercutting geometries, protruding from the metal component, are inserted into a locally infrared heated CFRT component. The aim is to investigate the joining process with a focus on the filling of the undercut features with matrix and fibers to create a primarily form-fitting joint. For good mechanical properties of the joint, it is crucial, that the undercutting features are filled and do not lead to significant deconsolidations. The pin structures are manufactured from 42CrMo4 steel on a cnc-lathe and are joined via welding with HCT600+Zn sheet metal. The CFRT samples are manufactured from polypropylene and approximately 45% vol. unidirectional glass fibers. In the scope of this study, different pin geometries are joined with varying process settings and micro sections of the joints are investigated via reflected light microscopy. It could be shown that the undercuts can be completely filled with matrix and fiber material using the described process route. Based on the optical investigations a suitable setting of joining parameters is defined and lap shear as well as cross head samples are manufactured and experimentally tested. It could be seen that independently from the pin geometry the lap shear strength was primarily limited due to shear failure of the pin structures and it is assumed that the base diameter and pin strength predominantly determine the joint strength. Cross head samples failed due to pin extraction. Here, a significant increase of the joint strength with undercutting features could be shown in comparison to cylindrical reference pins.

Effect of the tool geometry on microstructure and geometrical features of clinched aluminum - Ewenz, L.; Kuczyk, M.; Zimmermann, M. (Journal of Advanced Joining Processes)
In addition to brazing and welding processes, mechanical joining processes such as clinching are increasingly being used. Clinch joints offer an advantage over metallurgical joining processes by giving the possibility of joining different material combinations without typical drawbacks. Thereby clinching offers an enormous advantage for lightweight construction. An additional benefit is a great variability in the geometric shapes of the toolsets, which ensure optimum adaptation of the clinching process on variations of the joining elements such as e.g. the sheet thickness. However, the vast variability is also one of the major challenges regarding the prediction of the joint reliability. In the work presented, the effect of different toolset geometries was investigated with a particular focus on the interaction between geometrical features and deformation-induced microstructural changes. Light optical and electron microscopy techniques, as well as micro-hardness measurements, were performed. The results were evaluated and discussed concerning the material's deformation behavior, the change in geometrical shape and the microstructural evolution due to the different tool geometries. The findings point out the main influence factors regarding the mechanical properties in general and the fatigue behavior in particular.

Forming process induced material structure of fibre-reinforced thermoplastics - Experimental and numerical investigation of a bladder-assisted moulding process - Gröger, B.; Würfel, V.; Hornig, A.; Gude, M. (Journal of Advanced Joining Processes)

Investigation of the influence of the tumbling angle on a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (Production Engineering)
To achieve the climate objectives, various measures are taken to increase the efficiency of raw materials and energies used. A sector with a large proportion of the global consumption of resources is the mobility sector. To increase the efficiency in this field, large efforts are made to reduce the weight of moving masses. One approach is the use of multi-material systems, which utilises different materials and their specific properties depending on the local requirements. Multi-material systems consist often of materials which differ in strength and density, for example, high-strength steels, aluminium alloys or polymers. Additionally, such a system can utilise different geometries of the components to be joined, characterised for example by varying sheet thicknesses. A central challenge of producing these systems is the joining of the individual components. This requires robust joining processes capable of covering the entire spectrum of possible variants and is feasible for different physical properties of the materials. Since conventional joining processes are rather rigid and have difficulty reacting to changing process and disturbance variables, new joining processes are necessary. With the objective of being able to react versatile to varying parameters, a process combination consisting of a semi-tubular self-piercing riveting process and orbital forming process with adjustable tumbling kinematic is introduced. Due to the process combination of tumbling and self-piercing riveting, mutual influences of the two process components are analysed in regard to material flow and process forces. Further, the investigations show the influence of a varying tumbling angle on the joining process itself and how the characteristic properties undercut, rivet head end position and residual sheet thickness of the joint are affected. The material used for the joining partners is an aluminium alloy EN AW-6014 typical for multi-material systems in the automotive industry and the rivets are from type Rivset C produced by the Böllhoff company.

Analysis of the interactions between joint and component properties during clinching - Steinfelder, C.; Acksteiner, J.; Guilleaume, C.; Brosius, A. (Production Engineering)
Clinching is a joining process that is becoming more and more important in industry due to the increasing use of multi-material designs. Despite the already widespread use of the process, there is still a need for research to understand the mechanisms and design of clinched joints. In contrast to the tool parameters, process and material disturbances have not yet been investigated to a relatively large extent. However, these also have a great influence on the properties and applicability of clinching. The effect of process disturbances on the clinched joint are investigated with numerical and experimental methods. The investigated process variations are the history of the sheets using the pre-hardening of the material, different sheet thicknesses, sheet arrangements and punch strokes. For the consideration of the material history, a specimen geometry for pre-stretching specimens in uniaxial tension is used, from which the pre-stretched secondary specimens are taken. A finite element model is set up for the numerical investigations. Suitable clinching tools are selected. With the simulation, selected process influences can be examined. The effort of the numerical investigations is considerably reduced with the help of a statistical experimental design according to Taguchi. To confirm the simulation results, experimental investigations of the clinch point geometry by using micrographs and the shear strength of the clinched joint are performed. The analysis of the influence of difference disturbance factors on the clinching process demonstrate the importance of the holistic view of the clinching process.

Application of an edge detection algorithm for surface determination in industrial X-ray computed tomography - Busch, M.; Hausotte, T. (Production Engineering)
Surface determination is an essential step of the measurement process in industrial X-ray computed tomography (XCT). The starting point of the surface determination process step is a single grey value threshold within a voxel volume in conventional surface determination methods. However, this value is not always found in the reconstructed volume in the local environment of the surface of the measurement object due to various artefacts, so that none or incorrect surfaces are determined. In order to find surfaces independently of a single grey value, a three-dimensional approach of the initial contour determination based on a Prewitt edge detection algorithm is presented in this work. This method is applied to different test specimens and specimen compositions which, due to their material or material constellation, their geometric properties with regard to surfaces and interfaces as well as their calibrated size and length dimensions, embody relevant properties in the examination of joining connections. It is shown that by using the surface determination method in the measurement process, both a higher metrological structure resolution and interface structure resolution can be achieved. Surface artefacts can be reduced by the application and it is also an approach to improved surface finding for the multi-material components that are challenging for XCT.

Design of clinched joints on the basis of binding mechanisms - Kalich, J.; Füssel, U. (Production Engineering)
The work carried out is based on the thesis properties of clinched joints are determined by the proportions of binding mechanisms form-closure, force-closure and material-closure. To describe the acting binding mechanisms and thus to derive the joint properties, detailed knowledge of the local effect of the individual binding mechanisms is necessary to ensure their targeted adjustment by the joining process. The targeted setting of different proportions of the binding mechanisms is achieved firstly via tool geometry and secondly via surface condition of the joined parts. An introduced form-closure component can be quantified by metallographic cross section with subsequent measurement of the quality-determining parameters such as undercut, penetration depth and neck thickness. To qualify the force-closure component, a torsional load can be applied mechanically at rotationally symmetrical clinch joints. This also allows the influence of different surface conditions on the tribological system to be quantified. Measurement of electrical resistance can reveal the binding mechanisms of force- and material-closure. These investigations are carried out on an aluminum joining part combination of the same type. As a result of these investigations, the clinched joints can be designed according to the load occurring in the later life cycle in the form of an optimum and compromise variant with regard to minimum loads to be transmitted mechanically, electrically with regard to low resistance or manufacturing with minimum energy input.

Observations on additive plasticity in the logarithmic strain space at excessive strains - Friedlein, J.; Mergheim, J.; Steinmann, P. (International Journal of Solids and Structures)
Additive plasticity in the logarithmic strain space is compared to multiplicative plasticity for various loading cases including coaxial and non-coaxial plastic deformations. Even though both finite plasticity approaches are based on total Lagrangian descriptions, the former is popular due to its inherent similarity to the infinitesimal theory and its easy extensibility. However, since its introduction several limitations of additive plasticity in the logarithmic strain space have been discovered. In this study, these problems such as stress rotation and softening are considered, revealing that fundamental differences compared to multiplicative plasticity occur for non-coaxial plastic deformations. We focus in particular on the observed softer response of the additive based approach, which is analysed in depth using three numerical examples including two well-known benchmarks for finite plasticity. By means of these finite element simulations the softer and possibly even localising response of additive plasticity in the logarithmic strain space is confirmed.

Ecological Validity in Exercise Neuroscience Research: A Systematic Investigation - Chang, M.; Büchel, Daniel; Reinecke, K.; Lehmann, T.; Baumeister, Jochen (European Journal of Neuroscience)
Keywords: General Neuroscience

Use What You Know: Network and Service Coordination Beyond Certainty - Werner, Stefan; Schneider, Stefan Balthasar; Karl, Holger (IEEE/IFIP Network Operations and Management Symposium (NOMS))
Modern services often comprise several components, such as chained virtual network functions, microservices, or machine learning functions. Providing such services requires to decide how often to instantiate each component, where to place these instances in the network, how to chain them and route traffic through them. To overcome limitations of conventional, hardwired heuristics, deep reinforcement learning (DRL) approaches for self-learning network and service management have emerged recently. These model-free DRL approaches are more flexible but typically learn tabula rasa, i.e., disregard existing understanding of networks, services, and their coordination. Instead, we propose FutureCoord, a novel model-based AI approach that leverages existing understanding of networks and services for more efficient and effective coordination without time-intensive training. FutureCoord combines Monte Carlo Tree Search with a stochastic traffic model. This allows FutureCoord to estimate the impact of future incoming traffic and effectively optimize long-term effects, taking fluctuating demand and Quality of Service (QoS) requirements into account. Our extensive evaluation based on real-world network topologies, services, and traffic traces indicates that FutureCoord clearly outperforms state-of-the-art model-free and model-based approaches with up to 51% higher flow success ratios.
Keywords: network management; service management; AI; Monte Carlo Tree Search; model-based; QoS

Weight-optimized Battery Housings for Volume Vehicles - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson (ATZ worldwide)

Methodenentwicklung zur rechnerischen Auslegung geklebter Stahlverbindungen unter Alterungsbeanspruchung im Stahl- und Anlagenbau - Sander, Sascha; Teutenberg, Dominik; Meschut, Gerson; Kötz, Fabian; Matzenmiller, Anton; Kasper, Yann; Ummenhofer, Thomas (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Attention triggers and investors' risk-taking - Arnold, Marc; Pelster, Matthias; Subrahmanyam, Marti G. (Journal of Financial Economics)
The paper investigates the impact of individual attention on investor risk-taking. We analyze a large sample of trading records from a brokerage service that allows its customers to trade contracts-for-differences (CFD), and sends standardized push messages on recent stock performance to its client investors. The advantage of this sample is that it allows us to isolate the "push" messages as individual attention triggers, which we can directly link to the same individuals' risk-taking. A particular advantage of CFD trading is that it allows investors to make use of leverage, which provides us a pure measure of investors' willingness to take risks that is independent of the decision to purchase a particular stock. Leverage is a major catalyst of speculative trading, as it increases the scope of extreme returns, and enables investors to take larger positions than what they can afford with their own capital. We show that investors execute attention-driven trades with higher leverage, compared to their other trades, as well as those of other investors who are not alerted by attention triggers.

The Scale4Edge RISC-V Ecosystem - Ecker, Wolfgang; Adelt, Peer; Müller, Wolfgang; Heckmann, Reinhold; Krstic, Milos; Herdt, Vladimir; Drechsler, Rolf; Angst, Gerhard; Wimmer, Ralf; Mauderer, Andreas; Stahl, Rafael; Emrich, Karsten; et al. (In Proceedings of the Design Automation and Test Conference and Exhibition (DATE 2022))
This paper introduces the project Scale4Edge. The project is focused on enabling an effective RISC-V ecosystem for optimization of edge applications. We describe the basic components of this ecosystem and introduce the envisioned demonstrators, which will be used in their evaluation.

Gewichtsoptimierte Batteriegehäuse für Volumenfahrzeuge - Schmolke, Tobias; Krüger, Christopher; Merdivan, David; Meschut, Gerson (ATZ - Automobiltechnische Zeitschrift)

Durch Andere sich selbst erzählen: Figuren der Selbststilisierung in autobiographischen Schriften von Alan Bennett und Candia McWilliam - Mildorf, Jarmila (Erzählte Welt: Sinnstiftung in Zeiten kultureller und politischer Umbrüche)

Decision Support for Disaster Relief: Coordinating Spontaneous Volunteers - Sperling, Martina; Schryen, Guido (European Journal of Operational Research (EJOR))

Aligning strategic position, behavior, and structure for smart service businesses in manufacturing - Koldewey, Christian; Rasor, Anja; Reinhold, Jannik; Gausemeier, Jürgen; Dumitrescu, Roman; Chohan, Nadia; Frank, Maximilian (Technological Forecasting and Social Change)

Towards a model- and data-focused taxonomy of XAI systems - Kucklick, Jan-Peter (Wirtschaftsinformatik 2022 Proceedings)
Explainable Artificial Intelligence (XAI) is currently an important topic for the application of Machine Learning (ML) in high-stakes decision scenarios. Related research focuses on evaluating ML algorithms in terms of interpretability. However, providing a human understandable explanation of an intelligent system does not only relate to the used ML algorithm. The data and features used also have a considerable impact on interpretability. In this paper, we develop a taxonomy for describing XAI systems based on aspects about the algorithm and data. The proposed taxonomy gives researchers and practitioners opportunities to describe and evaluate current XAI systems with respect to interpretability and guides the future development of this class of systems.
Keywords: Explainable Artificial Intelligence; XAI; Interpretability; Decision Support Systems; Taxonomy

ReconROS Executor: Event-Driven Programming of FPGA-accelerated ROS 2 Applications - Lienen, Christian; Platzner, Marco

Digitalization of work: Challenges for workplace learning - Harteis, Christian; Goller, Michael; Gerholz, Karl-Heinz (The SAGE Handbook of Learning and Work)
The digitalization of workplaces can introduce changes on various levels of work activities. Educational research follows this transformation in one of two ways: On the one hand, there is the optimistic perspective of expecting to improve the quality of work and work life; on the other hand, there is the expectation that conditions of work and work life will generally deteriorate. Irrespective of the concrete outcomes of digitalization, a general agreement exists that digitalization will induce changes at workplaces that affect individuals and the tasks they do. At the same time, however, scholars disagree as to whether employees experience these changes in terms of affordances that engage them into learning new processes or if they experience constraints that inhibit further engagement in learning. This chapter explores the particular developments covered under the topic of digitalization at and of work, explains particular challenges of the introduction of cyber-physical systems and analyzes consequences for workplace learning. It focuses on conceptual change as a theoretical framework for understanding the quality of learning processes that seem inevitable in order to cope with the new requirements and – more importantly – to use the potentials of the new technologies. It then sketches the poor state of empirical research conducted in this area – so far limited to exploratory field studies – even in times of corona, which has boosted the digital transformation. The chapter ends with a description of the potential and problems of – at best interdisciplinary – research into learning at digitalized workplaces.

Die Relevanz von Mentor*innen für die Professionalisierung von angehenden Lehrkräften im Praxissemester: Forschungsdesiderate und Handlungsoptionen - Caruso, Carina; Goller, Michael (Die Deutsche Schule)
Im Praxissemester (PS) sind Mentor*innen für Studierende wichtige Bezugspersonen, die sie u. a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im PS mehrere Erkenntnisse vorliegen, ist die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Bericht zielt darauf, die Relevanz von Mentor*innen herauszuarbeiten, Forschungsdesiderate zu umreißen und Handlungsoptionen aufzuzeigen.
Keywords: Schlagwörter: Mentoring; Praxissemester; Professionalisierung

More Efficient Techniques for Adaptively-Secure Cryptography - Niehues, David
Modern-day communication has become more and more digital. While this comes with many advantages such as a more efficient economy, it has also created more and more opportunities for various adversaries to manipulate communication or eavesdrop on it. The Snowden revelations in 2013 further highlighted the seriousness of these threats. To protect the communication of people, companies, and states from such threats, we require cryptography with strong security guarantees. Different applications may require different security properties from cryptographic schemes. For most applications, however, so-called adaptive security is considered a reasonable minimal requirement of security. Cryptographic schemes with adaptive security remain secure in the presence of an adversary that can corrupt communication partners to respond to messages of the adversaries choice, while the adversary may choose the messages based on previously observed interactions. While cryptography is associated the most with encryption, this is only one of many primitives that are essential for the security of digital interactions. This thesis presents novel identity-based encryption (IBE) schemes and verifiable random functions (VRFs) that achieve adaptive security as outlined above. Moreover, the cryptographic schemes presented in this thesis are proven secure in the standard model. That is without making use of idealized models like the random oracle model.
Keywords: public-key cryptography; lattices; pairings; verifiable random functions; identity-based encryption

Early timing analysis based on scenario requirements and platform models - Holtmann, Jörg; Deantoni, Julien; Fockel, Markus (Software and Systems Modeling)
Distributed, software-intensive systems (e.g., in the automotive sector) must fulfill communication requirements under hard real-time constraints. The requirements have to be documented and validated carefully using a systematic requirements engineering (RE) approach, for example, by applying scenario-based requirements notations. The resources of the execution platforms and their properties (e.g., CPU frequency or bus throughput) induce effects on the timing behavior, which may lead to violations of the real-time requirements. Nowadays, the platform properties and their induced timing effects are verified against the real-time requirements by means of timing analysis techniques mostly implemented in commercial-off-the-shelf tools. However, such timing analyses are conducted in late development phases since they rely on artifacts produced during these phases (e.g., the platform-specific code). In order to enable early timing analyses already during RE, we extend a scenario-based requirements notation with allocation means to platform models and define operational semantics for the purpose of simulation-based, platform-aware timing analyses. We illustrate and evaluate the approach with an automotive software-intensive system.
Keywords: Modeling and Simulation; Software

The HSP40 chaperone Ydj1 drives amyloid beta 42 toxicity - Ring, Julia; Tadic, Jelena; Ristic, Selena; Poglitsch, Michael; Bergmann, Martina; Radic, Nemanja; Mossmann, Dirk; Liang, YongTian; Maglione, Marta; Jerkovic, Andrea; Hajiraissi, Roozbeh; Hanke, Marcel; et al. (EMBO Molecular Medicine)
Keywords: Molecular Medicine

Metamodellbasierte Prozesskette - Umformen-Schneiden-Spannen-Fügen - Heyser, Per; Meschut, Gerson; Nehls, Thomas; Scharr, Christian; Froitzheim, Pascal; Flügge, Wilko; Wiesenmayer, Sebastian; Merklein, Marion (Pressen, Systeme, Prozesse der Zukunft Effizienz + Digitalisierung)

Konzeption einer adaptiven Prozesskette für das mechanische Fügen - Meschut, Gerson; Heyser, Per; Merklein, Marion; Wiesenmayer, Sebastian; Flügge, Wilko; Scharr, Christian; Nehls, Thomas

Smart process chain – data analysis in sheet metal processing for joinability prediction - Heyser, Per; Wiesenmayer, Sebastian; Nehls, Thomas; Scharr, Christian; Flügge, Wilko; Merklein, Marion; Meschut, Gerson (SMART PRODUCTION 2022: DIGITALIZING AUTOMOTIVE MANUFACTURING)

Investigating the argumentation structures of EFL learners from diverse language backgrounds - Chen, Mei-Hua; Mudgal, Garima; Chen, Wei-Fan; Wachsmuth, Henning (EUROCALL)

Entwicklung eines innovativen Trennapparates zur Stickstoffrückgewinnung aus landwirtschaftlichen Abfällen - Bernemann, Sören Antonius; Maćkowiak, Jan; Maćkowiak, Jerzy; Bertling, René; Lutters, Nicole; Kenig, Eugeny

Stress-Aware Periodic Test of Interconnects - Sadeghi-Kohan, Somayeh; Hellebrand, Sybille; Wunderlich, Hans-Joachim (Journal of Electronic Testing)
Safety-critical systems have to follow extremely high dependability requirements as specified in the standards for automotive, air, and space applications. The required high fault coverage at runtime is usually obtained by a combination of concurrent error detection or correction and periodic tests within rather short time intervals. The concurrent scheme ensures the integrity of computed results while the periodic test has to identify potential aging problems and to prevent any fault accumulation which may invalidate the concurrent error detection mechanism. Such periodic built-in self-test (BIST) schemes are already commercialized for memories and for random logic. The paper at hand extends this approach to interconnect structures. A BIST scheme is presented which targets interconnect defects before they will actually affect the system functionality at nominal speed. A BIST schedule is developed which significantly reduces aging caused by electromigration during the lifetime application of the periodic test.
Keywords: Electrical and Electronic Engineering